Pengaruh Model Cooperative Learning Tipe Jigsaw terhadap Kemampuan Memahami Teks Narasi pada Siswa SMP : The Effect of the Jigsaw Type Cooperative Learning Model on Students’ Narrative Text Comprehension at SMP - Sari, Maulida (Universitas Tidar, 2025)
This study aims to desxribe the effect of the Jigsaw type of Cooperative Learning model on students’ ability to comprehend narrative texts. The method used was quantitative with a quasi-experimental design. The reseach population cinsisted of 156 seventh-grade students of SMP IT Darfaqih Qur’ani, spread across five classes. A total of 64 students were selescted as the sample, comprising an experimental class (VII Kadijah) that receives instruction using the Jigsaw model and a control class (VII Aisyah) that received conventional teaching. The research instrument was a narrative text comprehension test administered in both pre-test and post-test formats. The results of the normality and homogeneity tests indicates that the data were normally distributed and homogeneous. The paired t-test revealed a significant difference between the pre-test and post-test scores with a Sig. (2-tailed) value of 0,000 < α (0,05). The students’ average score increased frim 50,5 in the pre-test to 81,32 in the post-test, indicating a 58,82% improvement. These finding suggest that the Jigsaw Cooperative Learning model is effective in improving students’ narrative text comprehension and can be considered a participatory and applicable alternative strategy in Indonesia Language instruction at the junior high school level.